Wet Etching: Controlling the Facet of ZnO during Wet Chemical Etching Its (0001¯) O‐Terminated Surface (Small 14/2020). Issue 14 (14th April 2020) - Sun, Mei; Yu, Bocheng; Hong, Mengyu; Li, Zhiwei; Lyu, Fengjiao; Li, Xing; Li, Zhihong; Wei, Xianlong; Zhang, Zheng; Zhang, Yue; Chen, Qing
Abstract : In article number 1906435, Qing Chen and co‐workers obtain high‐index 01 1 ¯ 3 ¯ facets of ZnO during wet chemical etching of the (000 1 ¯ ) O‐terminated surface of ZnO and also provide the direct experimental evidence of the micromasking mechanism for the hillocks formation via an in situ liquid cell transmission electron microscopy study.